2021
DOI: 10.1186/s40824-021-00242-6
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in therapeutic strategies for repairing endometrial tissue in intrauterine adhesion

Abstract: Intrauterine adhesion (IUA) is a common gynaecological disease that develops from infection or trauma. IUA disease may seriously affect the physical and mental health of women of childbearing age, which may lead to symptoms such as hypomenorrhea or infertility. Presently, hysteroscopic transcervical resection of adhesion (TCRA) is the principal therapy for IUAs, although its function in preventing the recurrence of adhesion and preserving fertility is limited. Pharmaceuticals such as hormones and vasoactive ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 124 publications
0
41
0
15
Order By: Relevance
“…PDE5 inhibitors administration are contraindicated in people who are affected with headaches, hypotension, and flushing. 60 So it is better to use alternative methods such as hormone therapy or with caution, use lower doses in combination with other endometrial thickeners treatments. On the other hand, it should be noted that each drug has its unique effects which should be prescribed according to the patient's condition and underlying problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PDE5 inhibitors administration are contraindicated in people who are affected with headaches, hypotension, and flushing. 60 So it is better to use alternative methods such as hormone therapy or with caution, use lower doses in combination with other endometrial thickeners treatments. On the other hand, it should be noted that each drug has its unique effects which should be prescribed according to the patient's condition and underlying problem.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sildenafil in addition to enhancing blood flow to the uterus, can improve the ovulation success rate and decrease natural killer cell activity, which may be desired treatment for women with recurrent miscarriages. 12,60 One of the limitations of the reviewed studies is the lack of consideration to the side effects of PDE5 inhibitors in some studies and also the lack of evaluation of their outcome in different phases of ART. If so, most studies have evaluated ET on trigger day or the day before (Starting hCG treatment) in fresh cycle embryo transfer or at the end of the estrogen phase during the frozen embryo transfer (FET) period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The d-ECM can mimic the native environment under in vitro conditions (e.g., by creating a biomimetic environment allowing for the growth of stromal cells). Recent studies have confirmed that biomaterials with tissue-specific ECM features can improve regeneration and support gestation in a severe uterine damage model ( Miyazaki and Maruyama, 2014 ; Campo et al, 2021 ), thus demonstrating the value of decellularized tissues ( Ma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 93%
“…The introduction of various biological substances that stimulate tissue regeneration can promote endometrial injury repair ( Cervelló et al, 2015 ; Almeida et al, 2021 ; Ma et al, 2021 ). Stem cell therapy is currently the most attractive therapeutic approach to repairing endometrial damage ( Keyhanvar et al, 2021 ; Gharibeh et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%